Method for manufacturing positive electrode material for secondary battery

By forming and permeating the inner coating on the positive electrode material of NCM-type lithium composite transition metal oxide, the problem of battery performance deterioration caused by particle breakage during calendering is solved, and higher battery energy density and performance stability are achieved.

CN114730867BActive Publication Date: 2025-04-29LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080079831.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-06
Filing Date
2020-12-04
Publication Date
2025-04-29
Estimated Expiration
2040-12-04

AI Technical Summary

Technical Problem

In the positive electrode material of NCM type lithium composite transition metal oxide, particle rupture during calendering leads to exposure of the uncoated portion, causing side reactions with the electrolyte, thereby reducing battery performance.

Method used

The coating is formed on the surface of the NCM-type lithium composite transition metal oxide and performed post-treatment, including exposure to moisture with a relative humidity of 10% to 50%, followed by heat treatment to remove residual moisture, ensuring that the coating penetrates into the interior of the secondary particles.

Benefits of technology

The exposure of uncoated portions due to particle rupture is reduced, and the side reaction with the electrolyte is reduced, thereby improving the energy density and performance stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114730867B_ABST
    Figure CN114730867B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing a positive electrode material for a secondary battery, the method comprising: preparing a lithium composite transition metal oxide containing nickel, cobalt and manganese; forming a coating on the surface of the lithium composite transition metal oxide; and post-treating the lithium composite transition metal oxide with the coating formed thereon, wherein the post-treatment is performed by: exposing the lithium composite transition metal oxide with the coating formed thereon to moisture with a relative humidity of 10% to 50% at 25°C, and then heat-treating the lithium composite transition metal oxide to remove residual moisture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the priority of Korean Patent Application No. 10-2019-0162032 filed in the Korean Intellectual Property Office on December 6, 2019, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0004] The present invention relates to a method for manufacturing a positive electrode material for a secondary battery. Background Art

[0005] Recently, the rapid popularization of battery-powered electronic devices such as mobile phones, laptop computers and electric vehicles has led to a rapid increase in the demand for small, lightweight and relatively high-capacity secondary batteries. In particular, lithium secondary batteries have attracted much attention as driving power sources for portable electronic devices due to their light weight and high energy density. Therefore, extensive research and development work has been carried out to improve the performance of lithium secondary batteries.

[0006] In a lithium secondary battery in a state in which an organic electrolyte or a polymer electrolyte is filled between a negative electrode and a positive electrode, electric energy is generated by a redox reaction that occurs when lithium ions are intercalated into / deintercalated from the negative electrode and the positive electrode, both of which are made of an active material capable of intercalating and deintercalating lithium ions.

[0007] As a positive electrode active material for lithium secondary batteries, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), lithium manganese oxide (LiMnO 2 、LiMn 2 O 4 etc.), lithium iron phosphate compounds (LiFePO 4 ) etc. Among these materials, lithium cobalt oxide (LiCoO 2 ) has high operating voltage and excellent capacity characteristics, so it is widely used and used as a high-voltage positive electrode active material. However, due to the rising price and unstable supply of cobalt (Co), the large-scale use of LiCoO 2 As the power source for applications such as electric vehicles is limited, it is necessary to develop a new type of lithium-ion battery that can replace LiCoO. 2 positive electrode active material.

[0008] Therefore, a nickel-cobalt-manganese lithium composite transition metal oxide (hereinafter referred to as "NCM-type lithium composite transition metal oxide") has been developed, in which a portion of cobalt (Co) is replaced by nickel (Ni) and manganese (Mn). In order to solve the problems such as electrolyte decomposition and increased surface resistance that may be caused when the NCM-type lithium composite transition metal oxide contacts the electrolyte, surface coating of the NCM-type lithium composite transition metal oxide has been introduced. However, when the NCM-type lithium composite transition metal oxide is in the form of secondary particles formed by aggregation of primary particles, the secondary particles are broken and the uncoated parts are exposed during electrode calendering, resulting in side reactions with the electrolyte, so the performance of the battery is degraded. In this regard, there is still a need to develop a technology that can minimize the degradation of battery performance caused by particle rupture while maintaining the current calendering level to improve the electrode energy density. Summary of the invention

[0009] Technical issues

[0010] In the positive electrode material of NCM-type lithium composite transition metal oxide, the present invention provides a method for manufacturing a positive electrode material for a secondary battery, which can reduce the side reaction with the electrolyte caused by the exposure of the uncoated part to the inside due to particle rupture during compression, and reduce the degradation of battery performance by introducing the coating formed on the surface of the secondary particle into the interior of the secondary particle through post-treatment.

[0011] Technical Solution

[0012] The present invention provides a method for manufacturing a positive electrode material for a secondary battery, the method comprising: preparing a lithium composite transition metal oxide containing nickel, cobalt and manganese, forming a coating on the surface of the lithium composite transition metal oxide, and post-treating the lithium composite transition metal oxide with the coating formed thereon, wherein the post-treatment is performed by exposing the lithium composite transition metal oxide with the coating formed thereon to moisture with a relative humidity of 10% to 50% at 25°C, and then heat-treating the lithium composite transition metal oxide to remove residual moisture.

[0013] Beneficial Effects

[0014] According to the present invention, the coating formed on the surface of the secondary particles of the NCM-type lithium composite transition metal oxide can penetrate into the interior of the secondary particles by post-treatment. Therefore, even the surface of the primary particles inside the secondary particles is allowed to be coated, so even when particle rupture occurs during rolling, the coated surface of the primary particles is exposed, which can reduce the side reaction with the electrolyte caused when the uncoated portion is exposed inside, and thus reduce the degradation of battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 is a composition analysis image of a cross section of a positive electrode material manufactured according to Example 1;

[0016] Figure 2 is a composition analysis image of a cross section of a positive electrode material manufactured according to Comparative Example 1;

[0017] Figure 3 is a composition analysis image of a cross section of a positive electrode material manufactured according to Comparative Example 2;

[0018] Figure 4 This is a composition analysis image of the cross section of the positive electrode material manufactured according to Comparative Example 3. DETAILED DESCRIPTION

[0019] Hereinafter, the present invention will be described in detail to help understand the present invention. Here, it should be understood that the words or terms used in the specification and claims of the present invention should not be interpreted as limited to having the meaning defined in the commonly used dictionary. It should be further understood that the words or terms should be interpreted as having the meaning consistent with their meaning in the context of the relevant field and technical conception of the present invention based on the principle that the inventor can appropriately define the meaning of the words or terms to interpret the present invention in the best way.

[0020] <Method for producing positive electrode active material>

[0021] The present invention provides a method for manufacturing a positive electrode material for a secondary battery, the method comprising: preparing a lithium composite transition metal oxide containing nickel, cobalt and manganese, forming a coating on the surface of the lithium composite transition metal oxide, and post-treating the lithium composite transition metal oxide with the coating formed thereon, and the post-treatment is performed by: exposing the lithium composite transition metal oxide with the coating formed thereon to moisture with a relative humidity of 10% to 50% at 25°C, and then heat-treating the lithium composite transition metal oxide to remove residual moisture.

[0022] A method of manufacturing the positive electrode material will be described step by step in detail.

[0023] First, a lithium composite transition metal oxide containing nickel, cobalt, and manganese is prepared.

[0024] The lithium composite transition metal oxide is a NCM-type lithium composite transition metal oxide containing nickel (Ni), cobalt (Co) and manganese (Mn). The lithium composite transition metal oxide may be more preferably a high-Ni NCM-type lithium composite transition metal oxide, wherein the content of nickel (Ni) is 50 mol% or more relative to the total metal amount excluding lithium (Li). More preferably, the content of nickel (Ni) may be 60 mol% or more, more preferably 80 mol% or more. When the amount of nickel (Ni) satisfies the range of 50 mol% or more of the total metal content of the lithium composite transition metal oxide excluding lithium (Li), a higher capacity may be obtained.

[0025] The lithium transition metal oxide may be represented by Formula 1 below.

[0026] [Formula 1]

[0027] Li a Ni 1-b-c-d Co b Mn c Q d O 2+δ

[0028] In the above formula 1, Q is at least one element selected from the group consisting of Al, B, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr and Zr, and 1.0≤a≤1.5, 0 <b≤0.5,0<c≤0.5,0≤d≤0.1,0<b+c+d≤0.5,-0.1≤δ≤1.0。

[0029] In the lithium composite transition metal oxide of the above formula 1, the content (molar ratio) of Li may correspond to a, that is, 1.0≤a≤1.5. When a is less than 1.0, the capacity may be reduced, and when a is greater than 1.5, the particles are sintered during the firing process, so that the positive electrode active material may not be manufactured. Considering the significant improvement of the capacity characteristics of the positive electrode active material according to the content control of Li and the balance of sintering for manufacturing the active material, the content of Li may be more preferably 1.0≤a≤1.2.

[0030] In the lithium composite transition metal oxide of the above formula 1, the content (molar ratio) of Ni may correspond to 1-(b+c+d), for example, 0.5≤1-(b+c+d)<1. When the content of Ni in the lithium composite transition metal oxide of the above formula 1 is 0.5 or more, a sufficient amount of Ni that contributes to charging / discharging is ensured, which may thus lead to high capacity. More preferably, the content of Ni may be 0.60≤1-(b+c+d)≤0.99.

[0031] In the lithium composite transition metal oxide of Formula 1 above, the content (molar ratio) of Co may correspond to b, i.e., 0 < b ≤ 0.5. When the content of Co in the lithium composite transition metal oxide of Formula 1 above exceeds 0.5, there is a concern about an increase in cost. Considering that the capacity characteristics are significantly improved due to the inclusion of Co, the content of Co may more specifically be 0.05 ≤ b ≤ 0.2.

[0032] In the lithium composite transition metal oxide of Formula 1 above, the content (molar ratio) of Mn may correspond to c, i.e., 0 < c ≤ 0.5. When c in the lithium composite transition metal oxide of Formula 1 above exceeds 0.5, there is a concern that the output characteristics and capacity characteristics of the battery may deteriorate, and the content of Mn may more specifically be 0.05 ≤ c ≤ 0.2.

[0033] In the lithium composite transition metal oxide of Formula 1 above, Q may be a doping element included in the crystal structure of the lithium composite transition metal oxide, and the content (molar ratio) of Q may correspond to d, i.e., 0 ≤ d ≤ 0.1.

[0034] The lithium composite transition metal oxide may be secondary particles formed by aggregation of primary particles. In the present invention, a "primary particle" refers to the smallest particle unit that is distinguishable as a single piece when observing a cross-section of the positive electrode active material through a scanning electron microscope (SEM), and may be composed of a single crystal grain or multiple crystal grains. In the present invention, the average particle size of the primary particles can be measured by a method for measuring the size of each particle distinguishable in the cross-sectional SEM image of the positive electrode active material particles.

[0035] In the present invention, a "secondary particle" refers to a secondary structure formed by aggregation of multiple primary particles. The average particle size of the secondary particles can be measured using a particle size analyzer, and in the present invention, s3500 of Microtrac Co., Ltd. is used as the particle size analyzer.

[0036] Next, a coating is formed on the surface of the lithium composite transition metal oxide.

[0037] The method for forming the coating is not particularly limited, and a conventional coating treatment method for positive electrode materials for secondary batteries can be applied. For example, the lithium composite transition metal oxide and a coating source can be mixed, and then heat treatment can be performed to form a coating on the surface. For example, the coating source may be at least one selected from the following: Al(OH) 3 , Al 2 O 3 , H 3 BO 3 , B 2 O 3 , TiO 2 , TiO, Ti2 O 3 、Ti 3 O. Ti 2 O、Zr(OH) 4 、ZrO 2 、ZnO 2 Mg(OH) 2 MgO, H 2 WO 4 , WO 3 , VO, VO 2 、V 2 O 3 、V 2 O 5 , Ga 2 O.Ga 2 O 3 、In 2 O 3 、RuO 2 、RuO 4 、NbO、NbO 2 , Nb 2 O 5 、SnO、SnO 2 、Sr(OH) 2 After the coating sources are mixed, heat treatment may be performed in an air atmosphere, and may be performed at 100° C. to 600° C., more preferably, at 100° C. to 500° C. for 1 to 10 hours.

[0038] The coating formed as described above comprises a lithium metal oxide, wherein the lithium metal oxide comprises at least one selected from the group consisting of Al, B, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr and Zr. Specifically, the coating may comprise residual lithium byproducts on the surface of the lithium composite transition metal oxide, for example, LiOH and / or Li 2 CO 3 The coating layer may contain a lithium metal oxide formed by a reaction with a coating source. More preferably, the coating layer may contain a lithium metal oxide, and the lithium metal oxide includes at least one selected from Al, B and W. In this case, the lithium metal oxide may be a water-soluble compound. When the coating layer contains the water-soluble compound, the coating compound contained in the coating layer formed on the surface of the secondary particle can be effectively infiltrated into the secondary particle by post-treatment.

[0039] Next, the lithium composite transition metal oxide having the coating formed thereon is post-treated. In this case, the post-treatment is performed by exposing the lithium composite transition metal oxide having the coating formed thereon to moisture having a relative humidity of 10% to 50% at 25° C., and then heat-treating the lithium composite transition metal oxide to remove residual moisture.

[0040] The water-soluble lithium metal oxide contained in the coating can be dissolved in water and can penetrate from the surface of the secondary particle to the interior thereof by exposure to moisture in post-treatment. During the post-treatment, the relative humidity at 25°C can be 10% to 50%, more preferably 10% to 40%, and even more preferably 10% to 30%. When the relative humidity meets the above range, the coating can be uniformly formed on the surface and inside of the lithium composite transition metal oxide. When the relative humidity is less than 10%, it is difficult for the coating compound to penetrate into the interior of the secondary particle, making it difficult to form a coating on the surface of the primary particle, and when the relative humidity exceeds 50%, the coating compound penetrates too much into the interior of the secondary particle, making the coating formed on the surface of the secondary particle uneven, which may cause side reactions with the electrolyte on the surface of the secondary particle.

[0041] The moisture exposure within the above relative humidity range can be performed for 1 to 240 hours, more preferably 24 to 240 hours, more preferably 24 to 168 hours. When the moisture exposure is performed within the above relative humidity range, for the above time period, the coating compound contained in the coating formed on the surface of the secondary particle dissolves in the surface adsorbed moisture and effectively penetrates into the interior of the secondary particle, so that the coating compound can coat the surface of the primary particle.

[0042] After the moisture exposure, the lithium composite transition metal oxide is heat-treated to remove residual moisture. The heat treatment may be performed at 100° C. to 500° C., more preferably 200° C. to 400° C., more preferably 300° C. to 400° C. The heat treatment may be performed in an air atmosphere and may be performed for 1 to 10 hours, more preferably 4 to 6 hours.

[0043] By such post-treatment, the coating compound contained in the coating formed on the surface of the lithium composite transition metal oxide can be distributed to the surface of the primary particle inside the secondary particle. Therefore, even when particle breakage occurs during rolling, the coated surface of the primary particle is exposed, which can reduce the side reaction with the electrolyte caused when the uncoated portion is exposed inside, and thus reduce the degradation of battery performance.

[0044] <Positive Electrode and Lithium Secondary Battery>

[0045] According to another embodiment of the present invention, there are provided a positive electrode for a secondary battery including the positive electrode material manufactured as described above, and a lithium secondary battery.

[0046] Specifically, the positive electrode includes a positive electrode collector and a positive electrode material layer formed on the positive electrode collector and including the positive electrode material.

[0047] In the positive electrode, the positive electrode collector is not particularly limited as long as it has conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 to 500 μm, and in order to improve the adhesion of the positive electrode material, fine concavoconvexities can be formed on the surface of the collector. For example, the positive electrode collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0048] In addition, the positive electrode material layer may include a conductive material and a binder as well as the positive electrode material described above.

[0049] In this case, the conductive material is used to impart conductivity to the electrode, and any conductive material can be used without particular limitation as long as it has electronic conductivity without causing chemical changes in the battery to be constituted. Specific examples thereof may include graphite such as natural graphite or artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one of them or a mixture of two or more thereof can be used. The content of the conductive material may generally be 1% by weight to 30% by weight relative to the total weight of the positive electrode material layer.

[0050] In addition, the binder is used to improve the adhesion between the positive electrode material particles and the adhesion between the positive electrode material and the positive electrode collector. Its specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-to-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM rubber), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or their various copolymers, and any one or a mixture of two or more thereof can be used. Relative to the gross weight of the positive electrode material layer, the content of the binder may be 1% by weight to 30% by weight.

[0051] In addition to using the above-mentioned positive electrode material, the positive electrode can be prepared according to the conventional method for preparing the positive electrode. Specifically, a composition for forming a positive electrode material layer including the positive electrode material and a selective binder and a conductive material is applied to the positive electrode collector, and then the positive electrode can be prepared by drying and rolling the coated positive electrode collector. In this case, the types and contents of the positive electrode material, the binder and the conductive material are as described above.

[0052] The solvent may be a commonly used solvent in the art, and may be dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, etc., and any one thereof or a mixture of two or more thereof may be used. Considering the coating thickness and preparation yield of the slurry, if the solvent can dissolve or disperse the positive electrode material, the conductive material, and the binder, and thereafter has a viscosity that can show excellent thickness uniformity during the coating of the positive electrode, the amount of solvent to be used is sufficient.

[0053] Furthermore, in another method, the positive electrode may be prepared by casting a composition for forming a positive electrode material layer on a separate support and then laminating a film separated from the support on the positive electrode current collector.

[0054] According to another embodiment of the present invention, an electrochemical device including the positive electrode is provided. The electrochemical device may be a battery, a capacitor, etc., and more particularly may be a lithium secondary battery.

[0055] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode placed facing the positive electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, and the positive electrode is the same as above. In addition, the lithium secondary battery may also selectively include a battery shell for accommodating an electrode assembly consisting of the positive electrode, the negative electrode and the separator, and a sealing member for sealing the battery shell.

[0056] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0057] The negative electrode current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, the negative electrode current collector can generally have a thickness of 3 to 500 μm, and as in the case of the positive electrode current collector, fine concavoconvexities can be formed on the surface of the negative electrode current collector in order to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0058] In addition to the negative electrode active material, the negative electrode active material layer also selectively includes a binder and a conductive material. The negative electrode active material layer can be prepared by, for example, coating a composition for forming a negative electrode including a negative electrode active material and a selective binder and a conductive material on a negative electrode current collector, and then drying the negative electrode current collector; or the negative electrode active material layer can be prepared by casting the composition for forming a negative electrode on a separate support, and then laminating a film separated from the support on the negative electrode current collector.

[0059] Compounds capable of reversibly inserting and deinserting lithium can be used as the negative electrode active material. Specific examples of the negative electrode active material can be carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber and amorphous carbon; (semi)metallic materials that can be alloyed with lithium such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloy, Sn alloy or Al alloy; (semi)metallic oxides that can be doped and undoped with lithium such as SiO β (0<β<2), SnO 2 , vanadium oxide and lithium vanadium oxide; or, a composite of a (semi)metallic material and a carbonaceous material, such as a Si-C composite or a Sn-C composite, and any one of them or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as the negative electrode active material. In addition, low-crystalline carbon, high-crystalline carbon, etc. can be used as carbon materials. Typical examples of the low-crystalline carbon may include soft carbon and hard carbon, and typical examples of the high-crystalline carbon may include irregular, planar, flaky, spherical or fibrous natural graphite or artificial graphite, condensed graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesocarbon microbeads, mesophase pitch and high-temperature sintered carbon, such as coke derived from petroleum or coal tar pitch.

[0060] In addition, the binder and the conductive material may be the same as described above with respect to the positive electrode.

[0061] On the other hand, in a lithium secondary battery, a separator is used to separate the negative electrode from the positive electrode and to provide a path for lithium ions to move. Any separator can be used without particular limitation, as long as it is commonly used as a separator in a lithium secondary battery. In particular, a separator having a high water retention capacity for the electrolyte and a low resistance to the movement of electrolyte ions is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer and an ethylene / methacrylate copolymer, or a laminated structure having more than two layers. In addition, a typical porous nonwoven fabric can be used, for example, a nonwoven fabric formed of glass fiber, polyethylene terephthalate fiber, etc. having a high melting point. In addition, a coated separator including a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single layer or multilayer structure.

[0062] In addition, the electrolyte used in the present invention can be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc., all of which can be used in the manufacture of lithium secondary batteries, but are not limited thereto.

[0063] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0064] Any organic solvent can be used without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, the following substances can be used as organic solvents: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group and may include an aromatic ring or ether bond having a double bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or cyclopentane sulfone. Among these solvents, carbonate solvents are preferred, and a mixture of a cyclic carbonate having high ionic conductivity and a high dielectric constant (e.g., ethylene carbonate or propylene carbonate) and a linear carbonate compound having a low viscosity (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred as a mixture that can improve the charge / discharge performance of the battery.

[0065] Any compound can be used as the lithium salt without particular limitation as long as it can provide lithium ions used in the lithium secondary battery. Specifically, the following substances can be used as the lithium salt: LiPF 6 、LiClO 4 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlO 4 、LiAlCl 4 、LiCF 3 SO 3 ,LiC 4 F 9 SO 3 、LiN(C 2 F 5 SO 3 ) 2 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 、LiCl、LiI、LiB(C 2 O 4 ) 2 The lithium salt may be used in a concentration range of 0.1 M to 2.0 M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable conductivity and viscosity, thereby exhibiting excellent performance, and lithium ions may be efficiently moved.

[0066] In order to improve the life characteristics of the battery, inhibit the reduction of the battery capacity, and increase the discharge capacity of the battery, the electrolyte may further include one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum chloride, etc. In this case, the content of the additive may be 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.

[0067] The lithium secondary battery including the positive electrode material according to the present invention as described above stably exhibits excellent discharge capacity, output characteristics and capacity retention rate, and can therefore be used in portable devices such as mobile phones, notebook computers and digital cameras, and in the field of electric vehicles such as hybrid electric vehicles (HEVs).

[0068] Therefore, according to another embodiment of the present invention, there are provided a battery module including a lithium secondary battery as a unit battery, and a battery pack including the battery module.

[0069] The battery module or the battery pack can be used as a power source for one or more medium-to-large devices, such as power tools, electric vehicles such as electric vehicles (EV), hybrid electric vehicles (HEV) and plug-in hybrid electric vehicles (PHEV) or power storage systems.

[0070] Example

[0071] Hereinafter, embodiments of the present invention will be described in detail to ensure that those skilled in the art can easily implement the present invention. However, the present invention can be modified into other various forms and is not limited to the embodiments described herein.

[0072] Example 1

[0073] The coating source H 3 BO 3 LiNi composite transition metal oxide 0.7 Co 0.1 Mn 0.2 O 2 After mixing, the mixture was heat-treated at 400° C. for 5 hours in an air atmosphere to form a coating on the surface.

[0074] The lithium composite transition metal oxide having the coating formed thereon was placed in a chamber at 25° C. and 30% relative humidity and exposed to moisture for 48 hours. Then, the resultant was heat-treated at 400° C. for 5 hours to remove residual moisture, thereby obtaining a post-treated positive electrode material.

[0075] Comparative Example 1

[0076] The coating source H 3 BO 3 LiNi composite transition metal oxide 0.7 Co 0.1 Mn 0.2 O 2 The mixture was mixed and heat-treated at 400° C. for 5 hours in an air atmosphere to produce a positive electrode material having a coating formed on the surface. Thereafter, no post-treatment was performed.

[0077] Comparative Example 2

[0078] A post-treated positive electrode material was manufactured in the same manner as in Example 1, except that the lithium composite transition metal oxide having the coating layer formed thereon was placed in a chamber at 25° C. and a relative humidity of 5%.

[0079] Comparative Example 3

[0080] A post-treated positive electrode material was manufactured in the same manner as in Example 1, except that the lithium composite transition metal oxide having the coating layer formed thereon was placed in a chamber at 25° C. and a relative humidity of 60%.

[0081] Experimental Example 1: Composition Analysis of the Cross Section of the Positive Electrode Material

[0082] The positive electrode materials manufactured in Example 1 and Comparative Examples 1 to 3 were subjected to FIB (focused ion beam) treatment and NANO-SIMS analysis to analyze the composition of the cross section, thereby observing the composition of the coating layer that penetrated into the secondary particles. The results are shown in Figures 1 to 4 middle.

[0083] Figure 1 is a composition analysis image of a cross section of the positive electrode material according to Example 1, which shows that in the post-treated positive electrode material according to the present invention, the coating element 11 B is evenly distributed inside the secondary particles.

[0084] In contrast, Figure 2 is a composition analysis image of a cross section of the positive electrode material according to Comparative Example 1, which shows that in the positive electrode material without post-treatment, the coating element is distributed only on the surface of the secondary particles 11 B.

[0085] Figure 3 is a composition analysis image of a cross section of the positive electrode material according to Comparative Example 2, which shows that when post-treated at a relative humidity of less than 10%, the coating element 11 B is mainly present on the surface of the particles, with only a small amount of coating elements 11 B penetrated into the particles, so no uniform coating was formed inside the particles.

[0086] Figure 4 is a composition analysis image of a cross section of the positive electrode material according to Comparative Example 3, which shows that when post-treated at a relative humidity greater than 50%, the coating element 11 B penetrates too much into the interior of the particle, thus including an excess of coating elements inside the particle 11 B, but is not evenly coated on the interior and surface of the particles and is unevenly distributed.

[0087] Experimental Example 2: High Temperature Storage Evaluation

[0088] The various positive electrode materials manufactured in Example 1 and Comparative Examples 1 to 3, the carbon black conductive material and the PVdF binder were mixed in an N-methylpyrrolidone solvent in a weight ratio of 96:2:2 to prepare a positive electrode material mixture, and the mixture was coated on one surface of an aluminum current collector, dried at 100° C., and then rolled to prepare a positive electrode.

[0089] Artificial graphite, carbon black conductive material, and PVdF binder were mixed in an N-methylpyrrolidone solvent at a weight ratio of 96:2:2 to prepare a negative electrode material mixture, and the mixture was coated on one surface of a copper current collector, dried at 120° C., and then rolled to prepare a positive electrode.

[0090] A porous polyethylene separator is inserted between the positive electrode and the negative electrode prepared above to produce an electrode assembly, and the electrode assembly is placed inside the battery shell. Thereafter, an electrolyte is injected into the shell to produce a lithium secondary battery. In this case, the electrolyte is prepared by: 1.0M lithium hexafluorophosphate (LiPF 6 ) was dissolved in an organic solvent in which ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were mixed in a volume ratio of 3:4:3.

[0091] Each full-cell lithium secondary battery manufactured as described above was charged to 4.2V (termination current: 1 / 20C) at 0.7C at 25°C in CCCV mode, stored at a high temperature of 60°C for 4 weeks, and charged / discharged at a constant current of 0.5C in the range of 4.2V to 3.0V to measure the capacity retention rate and resistance change rate. The results are shown in Table 1.

[0092] [Table 1]

[0093] Capacity retention rate (%) Resistance change rate (%) Example 1 92.5 160.5 Comparative Example 1 87.3 190.1 Comparative Example 2 85.2 187.5 Comparative Example 3 75.4 231.5

[0094] Referring to Table 1, it is confirmed that Example 1 subjected to the post-treatment of the present invention has significantly improved capacity retention and reduced resistance change rate compared to Comparative Example 1 without post-treatment or Comparative Examples 2 and 3 having too low or too high relative humidity during post-treatment.

Claims

1. A method for manufacturing a positive electrode material for a secondary battery, the method comprising: preparing a lithium composite transition metal oxide containing nickel, cobalt and manganese; forming a coating on the surface of the lithium composite transition metal oxide; as well as The lithium composite transition metal oxide having the coating formed thereon is post-treated, Wherein, the post-processing is carried out by: exposing the lithium composite transition metal oxide having the coating formed thereon to moisture having a relative humidity of 10% to 50% at 25° C., The lithium composite transition metal oxide is then heat treated to remove residual moisture, The lithium composite transition metal oxide is a secondary particle formed by aggregation of primary particles; and the coating layer is distributed on the surface of the primary particles inside the secondary particles through the post-treatment.

2. The method of claim 1, wherein the coating comprises a lithium metal oxide, the lithium metal oxide comprising at least one selected from the group consisting of Al, B, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

3. The method according to claim 2, wherein the lithium metal oxide is a water-soluble compound. 4 . The method according to claim 3 , wherein the coating layer comprises a lithium metal oxide including at least one selected from the group consisting of Al, B and W. 5 . The method according to claim 1 , wherein the post-treatment is performed by exposing the lithium composite transition metal oxide having the coating layer formed thereon to moisture having a relative humidity of 10% to 30% at 25° C. 6 . The method according to claim 1 , wherein the post-treatment is performed by exposing the lithium composite transition metal oxide having the coating layer formed thereon to moisture for 1 hour to 240 hours.

7. The method according to claim 1, wherein the heat treatment for removing residual moisture is performed at 100°C to 500°C.

8. The method according to claim 1, wherein the heat treatment for removing residual moisture is performed for 1 hour to 10 hours.

9. The method according to claim 1, wherein the lithium composite transition metal oxide is represented by the following formula 1: [Formula 1] Li a Ni 1-b-c-d Co b Mr c Q d O 2+δ Wherein in the above formula 1, Q is at least one element selected from Al, B, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr and Zr, and 1.0≤a≤1.5,0 <b<0.5,0<c<0.5,0≤d≤0.1,0<b+c+d≤0.5,-0.1≤δ≤1.0。

Citation Information

Patent Citations

  • Active material for nonaqueous secondary battery and its manufacturing method

    CN101194383A

  • Method for manufacturing anode active material, and anode active material for lithium secondary battery manufactured thereby

    CN104781960A

  • Positive electrode material for lithium secondary battery and manufacturing method thereof

    CN106450175A

  • Lithium nickelate-based positive electrode active substance particles and process for producing the same, and non-aqueous electrolyte secondary battery

    CN109071266A